2012
DOI: 10.1177/0363546512454532
|View full text |Cite
|
Sign up to set email alerts
|

Second-Look Arthroscopic Assessment of Arthroscopic Single-Bundle Posterior Cruciate Ligament Reconstruction

Abstract: Satisfactory results were obtained for groups A and B in patients who underwent reconstruction for isolated PCL injury. However, 4 intraoperative complications (14.3%) were encountered with use of the Achilles tendon allograft (group B), with a relative higher rate of partial tear and less synovialization in the femoral aperture area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Critical application of the inclusion and exclusion criteria to those articles yielded 11 studies (Fig 1). 5,6,13,[15][16][17][18][19][20][21][22] The features of each of the included studies are listed in Table 4. Interestingly, there were no studies that had directly compared clinical outcomes after remnant-preserving PCLR with those after standard PCLR, and there were 2 studies with long-term follow-up.…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Critical application of the inclusion and exclusion criteria to those articles yielded 11 studies (Fig 1). 5,6,13,[15][16][17][18][19][20][21][22] The features of each of the included studies are listed in Table 4. Interestingly, there were no studies that had directly compared clinical outcomes after remnant-preserving PCLR with those after standard PCLR, and there were 2 studies with long-term follow-up.…”
Section: Literature Searchmentioning
confidence: 99%
“…Eight studies reported the outcomes of patients who underwent PCLR with remnant preservation. 5,9,13,15,19,[20][21][22] Among them, 1 study reported the outcomes of remnant-preserving PCLR with a minimum 10-year follow-up. Overall, Standard PCLR.…”
Section: Data Abstractionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, many centres routinely perform reconstructions of the PCL. Based on the initial diagnosis and associated structures, different surgical techniques and different grafts are used [3-12]. With surgical treatment, good clinical results and improved subjective patient outcomes can be achieved [13-17].…”
Section: Introductionmentioning
confidence: 99%